Psychosocial Functioning of Borderline Patients and Axis II Comparison Subjects Followed Prospectively for Six Years - Zanarini, Mary C.; Frankenburg, Frances R.; Hennen, John; Reich, D. Bradford; Silk, Kenneth R. (Journal of personality disorders, 2005)
The purpose of this study was to determine the course of the psychosocial functioning of patients with borderline personality disorder (BPD) over 6 years of prospective follow-up. The psychosocial functioning of 290 patients meeting both DIB-R and DSM-III-R criteria for BPD and 72 patients meeting DSM-III-R criteria for another Axis II disorder (and neither criteria set for BPD) was assessed at baseline using a semistructured interview of demonstrated reliability. Over 94% of surviving patients were reinterviewed about their psychosocial functioning blind to all previously collected information at three distinct follow-up waves: 2-, 4-, and 6-year follow-up. The psychosocial functioning of borderline patients improved substantially over time, with the percentage meeting criteria for good overall psychosocial functioning increasing from 26% at baseline to 56% during the third wave of follow-up. Despite this improvement, borderline patients functioned significantly more poorly than Axis II comparison subjects, particularly in the area of vocational achievement. However, a more detailed examination revealed that borderline patients who had experienced a symptomatic remission during the course of the study functioned significantly better both socially and vocationally than never-remitted borderline patients. More specifically, they were significantly more likely to have a good relationship with a spouse/partner and at least one parent, good work/school performance, a sustained work/school history, a GAF score of 61 or higher (43% vs. 0% 6 years after their index admission), and to have good overall psychosocial functioning (66% vs. 27% at 6 year follow-up). Taken together, the results of this study suggest that psychosocial improvement is both common among borderline patients and strongly related to their symptomatic status.